2017
DOI: 10.1371/journal.pone.0177530
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of older people with mild dementia and mild cognitive impairment and their relatives about falls risk and prevention: A qualitative study

Abstract: ObjectiveTo explore the perceptions of older people with mild dementia and mild cognitive impairment, and their family carers, about falling, falls risk and the acceptability of falls prevention interventions.DesignQualitative study involving thematic analysis of semi-structured interviews with patient and relative dyads.Participants and setting20 patient/ relative dyads recruited from Memory Assessment Services and Falls Prevention Services in the United Kingdom.ResultsThe findings are presented under four ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 41 publications
0
64
0
1
Order By: Relevance
“…However, in line with previous research recognising the role of carer in the advanced stages of dementia [47], we found that the person might lack the insight/capacity needed to develop and sustain intrinsic motivation, or they might forget that they are intrinsically motivated to change behaviour. As external motivation becomes pivotal [48], the level of commitment that the significant others have in supporting the person with dementia is essential. Previous studies [26][27][28] found that carers might be risk-averse and as a result, adopt gate-keeping behaviours to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in line with previous research recognising the role of carer in the advanced stages of dementia [47], we found that the person might lack the insight/capacity needed to develop and sustain intrinsic motivation, or they might forget that they are intrinsically motivated to change behaviour. As external motivation becomes pivotal [48], the level of commitment that the significant others have in supporting the person with dementia is essential. Previous studies [26][27][28] found that carers might be risk-averse and as a result, adopt gate-keeping behaviours to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of insight into deficits may have had moderating effects on the care recipients’ self‐reported self‐efficacy (Dawson, Powers, Krestar, Yarry, & Judge, ). Preparing for increasing care needs requires the person with dementia to consider and plan for future incapacity, a concept some would prefer to ignore (Mak & Sörensen, ; Peach et al., ). The stigma associated with dementia results in poor adjustment to the disease and subsequent reduction in self‐efficacy (Martin, Turner, Wallace, & Choudhry, ).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of insight into deficits may have had moderating effects on the care recipients' selfreported self-efficacy (Dawson, Powers, Krestar, Yarry, & Judge, 2012). Preparing for increasing care needs requires the person with dementia to consider and plan for future incapacity, a concept some would prefer to ignore (Mak & S€ orensen, 2012;Peach et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was developed by a multi-disciplinary team of physiotherapists, occupational therapists, doctors, nurses, psychologists, and patient and public representatives, using the principles of co-production. This was informed by findings from three literature reviews [ 92 94 ], clinician, health psychology and neuropsychological expertise ascertained by interview and during workshops, focus group discussions held with patients, carers, and clinicians, and the views of patients and their carers from a prior interview study [ 62 ]. Ten patients were treated in a 6-week ‘proof of concept’ study as part of the intervention development, in which intermediate outcomes were measured and field notes were thematically analysed.…”
Section: Methodsmentioning
confidence: 99%
“…behaviour change wheel [ 58 ]) in the context of dementia is unknown, but provides a framework for further investigation. Barriers to sustaining a moderate to vigorous exercise programme include not perceiving oneself as being at risk from falls; perceived lack of relevance of exercise or other interventions; and focus on priorities such as maintaining independence, or family, social or domestic concerns [ 62 64 ]. Barriers to long-term adherence include forgetfulness, medical co-morbidities, planning problems and practical support.…”
Section: Introductionmentioning
confidence: 99%